Pressure-sensitive adhesive composition, and pressure-sensitive adhesive film, surface protection film, and pressure-sensitive adhesive layer-attached optical film using the same
Patent Information
- Application Number
- JP2023196496
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-11-20
- Publication Date
- 2025-02-27
- Estimated Expiration
- 2038-09-27
AI Technical Summary
【0022】 本発明の表面保護フィルムは、その用途において被着体が、トリアセチルセルロース(TAC)、ポリエチレンテレフタレート(PET)、ポリメチルメタクリレート(PMMA)からなる基材群から選択された基材を用いた光学フィルムの表面に適用可能である。 本発明の表面保護フィルムは、これら被着体に対して、優れた粘着性能、耐汚染性能を有し、且つ優れた剥離帯電防止性能を有している。 さらに、本発明の表面保護フィルムは、該被着体の表面に、フッ素化合物を含有する防汚層、又は、フッ素化合物を含有する樹脂組成物を用いて低屈折率層が形成されている場合においても、優れた粘着性能、耐汚染性能を有し、且つ優れた剥離帯電防止性能を有している。 本発明によれば、優れた粘着性能とともに、帯電防止性能と、耐汚染性能との両立を図ることが可能な粘着剤組成物、及びそれを用いた粘着フィルム、表面保護フィルムを提供することができる。このため、本発明は、産業上の利用価値が極めて大である。 また、本発明の表面保護フィルムは、被着体に対して、優れた粘着性能、耐汚染性能を有し、且つ優れた剥離帯電防止性能を有している。 また、本発明に係わる、アクリル系ポリマーと、帯電防止剤と、無臭化精製されたポリエーテル変性シロキサン化合物とを含有する粘着剤組成物、及びそれを用いた粘着フィルム、表面保護フィルムは、優れた粘着性能とともに、帯電防止性能と、耐汚染性能との両立が図られている。 本発明において、アクリル系ポリマーと、帯電防止剤と、ポリエーテル変性シロキサン化合物として、無臭化精製されたポリエーテル変性シロキサン化合物とを含有する粘着剤組成物を用いて形成した粘着剤層が、優れた粘着性能とともに、帯電防止性能と、耐汚染性能との両立を図ることが可能となる理由は、明確ではない。想定される理由としては、例えば、ポリエーテル変性シロキサン化合物が無臭化精製されることで、ポリエーテル変性シロキサン化合物に含有されている副生成物が極めて少ない状態となり、アクリル系ポリマーとの相溶性が向上することにより、ポリエーテル変性シロキサン化合物のブリードアウトが生じないように分散性が改善されることなどが考えられる。
Smart Images

Figure 0007637213000001 
Figure 0007637213000002 
Figure 0007637213000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a pressure-sensitive adhesive composition containing an antistatic agent, and a pressure-sensitive adhesive film and a surface protection film using the same. More specifically, the present invention relates to a pressure-sensitive adhesive composition that can achieve both excellent adhesive performance, antistatic performance, and stain resistance, and to a pressure-sensitive adhesive film and a surface protection film using the same. [Background technology]
[0002] Conventionally, in a pressure-sensitive adhesive layer formed using a pressure-sensitive adhesive composition having antistatic properties, and in a surface protection film using the same, there has been a trade-off between the antistatic properties and the stain resistance of the adherend, and it has been difficult to improve the stain resistance while maintaining the antistatic properties. Furthermore, in recent years, the types of materials of the adherends to which the surface protective film is attached have been increasing. In addition, the surface of the adherend to which the surface protective film is attached also has a wide variety of surface conditions due to various surface treatments applied to the adherend. For this reason, it is becoming increasingly difficult to simultaneously satisfy antistatic performance and anti-contamination performance for all adherends.
[0003] In order to solve such problems, for example, a surface protection film using an adhesive composition containing an acrylic copolymer obtained by copolymerizing specific monomers at a specific ratio, an antistatic agent, and a compound containing fluorine or silicon in its structure has been proposed as an adhesive composition forming an adhesive layer of a surface protection film (Patent Document 1). In addition, the compound containing fluorine or silicon in its structure is selected from any one of polyether-modified polyorganosiloxane, fluorine-containing alkyl group-containing fluorine-based surfactant, and acrylic polymer containing fluorine or silicon in its structure. In addition, even if the adherend to which the surface protection film according to the invention described in Patent Document 1 is attached is a functional layer formed by hard coating treatment using a fluorine-containing compound or a silicon-containing compound, or by low reflection treatment or antifouling treatment using these compounds, the generation of static electricity itself is suppressed when the surface protection film is peeled off from the adherend, and the occurrence of problems such as adherend contamination due to peeling electrification and electronic circuit destruction due to sparks caused by peeling electrification can be suppressed.
[0004] It has also been proposed to form the adhesive layer of a surface protection film using an adhesive composition containing a first (meth)acrylic copolymer containing a first structural unit of a specific structure having a carboxy group and a second structural unit derived from a monomer having a hydroxy group, a polyether-modified silicone having a hydroxy group at the polyether terminal, and an alkali metal salt (Patent Document 2).The surface protection film according to the invention described in Patent Document 2 is said to be capable of achieving both high levels of antistatic performance and low contamination of the adherend. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 5544800 [Patent Document 2] Patent No. 6058390 Summary of the Invention [Problem to be solved by the invention]
[0006] Incidentally, the surface protection film related to the invention described in Patent Document 1 has a method for testing contamination of adherends as follows: "Each of the previously obtained surface protection films was attached to the surface of the functional layer side of the above-mentioned AG polarizing plate and HC polarizing plate by pressing it with a 2 kgf roller once back and forth. These samples were then left in an environment of 70°C for 3 days. Thereafter, the samples were removed and left at 23°C and 50% RH for 24 hours, after which the samples were peeled off from the adherend and the degree of contamination was visually observed and evaluated according to the following criteria" (paragraph
[0049] of Reference 1). However, the surface protection film of the invention described in Patent Document 1 does not disclose any information regarding its contamination resistance when stored under more severe test conditions, such as a high temperature and high humidity environment (for example, an atmosphere with a temperature of 60°C and a humidity of 90% RH). In addition, although cited document 1 describes polyether-modified polyorganosiloxane, it does not describe or suggest anything about the impurities contained in the compound or the adverse effects of these impurities on the staining properties of the adherend. Furthermore, the surface protection film related to the invention described in Patent Document 1 has an acrylic copolymer as the base polymer of the adhesive, and is copolymerized with a (meth)acrylic acid ester having an alkylene oxide group. Therefore, although the required antistatic performance and adhesive performance can be obtained, it is difficult to obtain a good balance of properties, including anti-fouling performance. In addition, the surface protection film according to the invention described in Patent Document 2 achieves both antistatic performance and contamination resistance by using a monomer component with a specific structure, such as a first structural unit with a specific structure containing a carboxy group, as the (meth)acrylic copolymer of the adhesive composition that forms the adhesive layer. However, there was a problem that it was difficult to obtain a pressure-sensitive adhesive layer having a sufficient balance of properties due to poor compatibility between the polyether-modified silicone contained in the pressure-sensitive adhesive composition and the first (meth)acrylic copolymer, and due to the adhesive performance of the first (meth)acrylic copolymer itself. In addition, although cited document 2 describes polyether-modified polyorganosiloxane, it does not describe or suggest anything about the impurities contained in the compound or the effect of the impurities on the staining of the adherend.
[0007] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide an adhesive composition that can achieve both excellent adhesive performance, antistatic performance, and anti-soiling performance, and an adhesive film and a surface protection film using the same. [Means for solving the problem]
[0008] The present inventors have discovered that a pressure-sensitive adhesive layer formed using a pressure-sensitive adhesive composition containing an acrylic polymer, an antistatic agent, and a deodorized and purified polyether-modified siloxane compound as a polyether-modified siloxane compound has excellent contamination resistance that prevents contamination of the surface of an adherend. In other words, the present inventors have found that there is a difference in the performance of the pressure-sensitive adhesive layer between a purified polyether-modified siloxane compound that does not contain impurities and a polyether-modified siloxane compound that contains impurities, in terms of the superiority or inferiority of antistatic performance and anti-staining performance, and have completed the present invention. The technical idea of the present invention is to provide a pressure-sensitive adhesive composition containing an acrylic polymer, an antistatic agent, and a deodorized and purified polyether-modified siloxane compound.
[0009] The pressure-sensitive adhesive composition of the present invention containing an antistatic agent and a deodorized and purified polyether-modified siloxane compound, and the pressure-sensitive adhesive film and surface protection film using the same, can achieve a balance between excellent adhesive performance, antistatic performance, and contamination resistance. The pressure-sensitive adhesive composition according to the present invention, and the pressure-sensitive adhesive film and surface protection film using the same have solved the problems of the conventional techniques.
[0010] In order to solve the above problems, the present invention provides a pressure-sensitive adhesive composition containing an acrylic polymer mainly composed of a (meth)acrylic acid alkyl ester, an antistatic agent, a crosslinking agent, and a polyether-modified siloxane compound, wherein the polyether-modified siloxane compound is a deodorized and purified polyether-modified siloxane compound, and the pressure-sensitive adhesive composition contains 0.01 to 1.0 part by weight of the deodorized and purified polyether-modified siloxane compound per 100 parts by weight of the acrylic polymer.
[0011] The deodorized and purified polyether-modified siloxane compound is preferably a polyether-modified siloxane compound having an HLB value of 4 to 15 and a weight average molecular weight of 10,000 or less from which by-products such as propenyl-etherified polyoxyalkylene and / or aldehyde condensates have been removed.
[0012] The acrylic polymer is an acrylic polymer consisting of a copolymer having an acid value of 0.1 to 1.0 and a weight average molecular weight of more than 300,000 and not more than 1,000,000, obtained by copolymerizing a total of 0.1 to 10 parts by weight of (B) at least one or more copolymerizable monomers containing a hydroxyl group and a total of 0.01 to 0.5 parts by weight of (C) at least one or more copolymerizable monomers containing a carboxyl group with a total of 100 parts by weight of (A) at least one or more (meth)acrylic acid ester monomers having an alkyl group carbon number of C1 to C18, and the (A) It is preferable that the adhesive composition contains 60 parts by weight or more of 2-ethylhexyl acrylate out of a total of 100 parts by weight of at least one (meth)acrylic acid ester monomer having an alkyl group carbon number of C1 to C18, the glass transition temperature of the acrylic polymer is 0°C or lower, the crosslinking agent is (D) a tri- or higher functional isocyanate compound, the antistatic agent is an ionic compound having a melting point of 25 to 50°C, and the adhesive composition further contains (E) a crosslinking retarder and (F) a crosslinking catalyst other than a tin compound as a crosslinking catalyst.
[0013] It is preferable that the antistatic agent is an ionic compound, the cation of the ionic compound is one selected from the group consisting of pyridinium, imidazolium, phosphonium, sulfonium, pyrrolidinium, guanidinium, ammonium, isouronium, thiouronium, piperidinium, pyrazolium, methylium, lithium, and morpholinium, and the ionic compound is contained as an essential component in a proportion of 0.01 to 10 parts by weight relative to 100 parts by weight of the acrylic polymer.
[0014] The pressure-sensitive adhesive layer obtained by crosslinking the pressure-sensitive adhesive composition has a surface resistivity of 1.0×10 +12 Ω / □ or less, the peeling electrification voltage of the pressure-sensitive adhesive layer relative to a low refractive index layer formed using a composition for forming a low refractive index layer containing a fluorine compound is within the range of +0.3 to −0.3 kV; the adhesive layer obtained by crosslinking the pressure-sensitive adhesive composition has an adhesive strength of 0.04 to 0.2 N / 25 mm at a low peel speed of 0.3 m / min and an adhesive strength of 2.0 N / 25 mm or less at a high peel speed of 30 m / min, to a polarizing plate having the low refractive index layer applied to a surface substrate; It is preferable that the adhesive layer obtained by crosslinking the adhesive composition is bonded to a polarizing plate having the low refractive index layer applied to a surface substrate, and then the plate is left for two days in an atmosphere having a temperature of 60°C and a humidity of 90% RH. After being removed from the atmosphere, one day later, the adhesive layer is peeled off from the polarizing plate without contamination.
[0015] the (B) hydroxyl group-containing copolymerizable monomer is at least one selected from the group consisting of 8-hydroxyoctyl(meth)acrylate, 6-hydroxyhexyl(meth)acrylate, 4-hydroxybutyl(meth)acrylate, 2-hydroxyethyl(meth)acrylate, N-hydroxy(meth)acrylamide, N-hydroxymethyl(meth)acrylamide, and N-hydroxyethyl(meth)acrylamide, The (C) carboxyl group-containing copolymerizable monomer is preferably at least one selected from the group consisting of (meth)acrylic acid, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, 2-(meth)acryloyloxyethyl hexahydrophthalic acid, 2-(meth)acryloyloxypropyl hexahydrophthalic acid, 2-(meth)acryloyloxyethyl phthalic acid, 2-(meth)acryloyloxyethyl succinic acid, 2-(meth)acryloyloxyethyl maleic acid, carboxypolycaprolactone mono(meth)acrylate, and 2-(meth)acryloyloxyethyl tetrahydrophthalic acid.
[0016] the pressure-sensitive adhesive composition comprises (E) a crosslinking retarder and (F) a crosslinking catalyst other than a tin compound, the (E) crosslinking retarder being a keto-enol tautomer compound, and the (E) crosslinking retarder is contained in an amount of 0.1 to 300 parts by weight per 100 parts by weight of the acrylic polymer, the (F) crosslinking catalyst is at least one metal chelate compound selected from the group consisting of an aluminum chelate compound, a titanium chelate compound, and an iron chelate compound, It is preferable that the (F) crosslinking catalyst is contained in a ratio of 0.001 to 0.5 parts by weight based on 100 parts by weight of the acrylic polymer, and the (E) / (F) weight part ratio is 80 to 1,000.
[0017] The present invention also provides a pressure-sensitive adhesive film, comprising a resin film and a pressure-sensitive adhesive layer formed by crosslinking the pressure-sensitive adhesive composition on one side of the resin film.
[0018] The present invention also provides a surface protection film using the above-mentioned pressure-sensitive adhesive film.
[0019] The present invention also provides a surface protection film for a polarizing plate, which uses the above-mentioned pressure-sensitive adhesive film.
[0020] The present invention also provides an optical film with a pressure-sensitive adhesive layer, comprising an optical film and a pressure-sensitive adhesive layer formed by crosslinking the pressure-sensitive adhesive composition, laminated on at least one surface of the optical film.
[0021] The present invention also provides a pressure-sensitive adhesive film, wherein one surface of the resin film opposite the surface on which the pressure-sensitive adhesive layer is formed is subjected to an antistatic treatment and an antifouling treatment. Effect of the Invention
[0022] The surface protection film of the present invention is applicable to the surface of an optical film in which the adherend in its application uses a substrate selected from the group of substrates consisting of triacetyl cellulose (TAC), polyethylene terephthalate (PET), and polymethyl methacrylate (PMMA). The surface protective film of the present invention has excellent adhesion and stain resistance to these adherends, and also has excellent antistatic properties upon peeling. Furthermore, the surface protection film of the present invention has excellent adhesion performance, contamination resistance, and excellent antistatic performance against peeling, even when an anti-fouling layer containing a fluorine compound or a low refractive index layer is formed on the surface of the adherend using a resin composition containing a fluorine compound. According to the present invention, it is possible to provide a pressure-sensitive adhesive composition capable of achieving both excellent adhesive performance, antistatic performance, and stain resistance, and a pressure-sensitive adhesive film and a surface protection film using the same. Therefore, the present invention has extremely high industrial utility value. Furthermore, the surface protective film of the present invention has excellent adhesion to adherends, excellent stain resistance, and excellent antistatic properties upon peeling. In addition, the adhesive composition according to the present invention, which contains an acrylic polymer, an antistatic agent, and a deodorized and purified polyether-modified siloxane compound, and the adhesive film and surface protection film using the same, are designed to achieve a balance between excellent adhesive performance, antistatic performance, and contamination resistance. In the present invention, the reason why the adhesive layer formed by using the adhesive composition containing acrylic polymer, antistatic agent, and deodorized and refined polyether-modified siloxane compound as polyether-modified siloxane compound can achieve both excellent adhesive performance, antistatic performance, and anti-staining performance is not clear.The assumed reason is that, for example, by deodorizing and refining polyether-modified siloxane compound, the by-product contained in polyether-modified siloxane compound becomes extremely small, and compatibility with acrylic polymer is improved, so that dispersibility of polyether-modified siloxane compound is improved so that bleeding out does not occur. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] Hereinafter, the present invention will be described based on preferred embodiments. The pressure-sensitive adhesive composition of the present invention is an adhesive composition containing an acrylic polymer mainly composed of a (meth)acrylic acid alkyl ester, an antistatic agent, a crosslinking agent, and a polyether-modified siloxane compound, characterized in that the polyether-modified siloxane compound is a deodorized and purified polyether-modified siloxane compound, and is contained in an amount of 0.01 to 1.0 part by weight per 100 parts by weight of the acrylic polymer.
[0024] The acrylic polymer used in the pressure-sensitive adhesive composition of the present embodiment is a main polymer of the pressure-sensitive adhesive composition, and is an acrylic polymer having a glass transition temperature of 0° C. or less. The acrylic polymer is preferably a copolymer mainly composed of (meth)acrylic acid ester monomers (A) having an alkyl group with carbon number of C1 to C18, among (meth)acrylic acid alkyl esters. Here, the proportion of the main component is preferably 50 parts by weight or more, more preferably 80 parts by weight or more, and particularly preferably 90 parts by weight or more, based on 100 parts by weight of the entire acrylic polymer.
[0025] (A) Examples of the (meth)acrylic acid ester monomers having an alkyl group with a carbon number of C1 to C18 include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl ( Examples of the alkyl (meth)acrylate monomer include isononyl (meth)acrylate, decyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, cyclopentyl (meth)acrylate, and cyclohexyl (meth)acrylate. The alkyl group of the alkyl (meth)acrylate monomer may be linear, branched, or cyclic.
[0026] The acrylic polymer used in the pressure-sensitive adhesive composition of this embodiment preferably contains 2-ethylhexyl acrylate in a proportion of 60 parts by weight or more, more preferably 70 parts by weight or more, and particularly preferably 80 parts by weight or more, of a total of 100 parts by weight of at least one (meth)acrylic acid ester monomer (A) having an alkyl group with a carbon number of C1 to C18.
[0027] In the acrylic polymer used in the pressure-sensitive adhesive composition of the present embodiment, examples of the monomer that can be copolymerized with (A) the (meth)acrylic acid ester monomer having an alkyl group with a carbon number of C1 to C18 include (B) a copolymerizable monomer containing a hydroxyl group and (C) a copolymerizable monomer containing a carboxyl group.
[0028] (B) The copolymerizable monomer containing a hydroxyl group may be at least one selected from the group consisting of 8-hydroxyoctyl(meth)acrylate, 6-hydroxyhexyl(meth)acrylate, 4-hydroxybutyl(meth)acrylate, 2-hydroxyethyl(meth)acrylate, N-hydroxy(meth)acrylamide, N-hydroxymethyl(meth)acrylamide, and N-hydroxyethyl(meth)acrylamide.
[0029] The acrylic polymer used in the pressure-sensitive adhesive composition of this embodiment preferably contains 0.1 to 10 parts by weight, more preferably 1.0 to 6.0 parts by weight, even more preferably 2.0 to 5.0 parts by weight, and particularly preferably 2.5 to 4.5 parts by weight of (B) at least one or more copolymerizable monomers containing a hydroxyl group, per 100 parts by weight of (A) at least one or more (meth)acrylic acid ester monomers having an alkyl group with a carbon number of C1 to C18.
[0030] (C) The copolymerizable monomer containing a carboxyl group may be at least one selected from the group consisting of (meth)acrylic acid, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, 2-(meth)acryloyloxyethyl hexahydrophthalic acid, 2-(meth)acryloyloxypropyl hexahydrophthalic acid, 2-(meth)acryloyloxyethyl phthalic acid, 2-(meth)acryloyloxyethyl succinic acid, 2-(meth)acryloyloxyethyl maleic acid, carboxypolycaprolactone mono(meth)acrylate, and 2-(meth)acryloyloxyethyl tetrahydrophthalic acid.
[0031] The acrylic polymer used in the pressure-sensitive adhesive composition of this embodiment preferably contains 0.01 to 0.5 parts by weight, more preferably 0.01 to 0.4 parts by weight, and particularly preferably 0.01 to 0.3 parts by weight of at least one or more copolymerizable monomers containing a carboxyl group (C) per 100 parts by weight of at least one or more (meth)acrylic acid ester monomers (A) having an alkyl group with a carbon number of C1 to C18.
[0032] The acrylic polymer used in the pressure-sensitive adhesive composition of this embodiment is preferably a copolymer having an acid value of 0.1 to 1.0 and a weight average molecular weight (Mw) of more than 300,000 and not more than 1,000,000. Mw is more preferably not more than 800,000, and even more preferably not more than 600,000. This contributes to improving the stain resistance. Here, the "acid value" is an index representing the acid content, and is expressed as the number of milligrams of potassium hydroxide required to neutralize 1 g of a polymer containing a carboxyl group.
[0033] The method for producing the acrylic polymer used in the pressure-sensitive adhesive composition of the present embodiment is not particularly limited, and any known polymerization method such as solution polymerization or emulsion polymerization can be used as appropriate. The monomers used for producing the acrylic polymer preferably include at least one of each of the above (A) to (C). Other monomers can be copolymerized within a range that does not impair the effects of the present invention.
[0034] The acrylic polymer used in the pressure-sensitive adhesive composition of the present embodiment is preferably a copolymer that does not contain a (meth)acrylic acid ester having an alkylene oxide group, in order to easily obtain a pressure-sensitive adhesive composition having an excellent balance of properties including adhesive performance. Here, examples of the (meth)acrylic acid ester having an alkylene oxide group include polyalkylene glycol mono(meth)acrylate, polyalkylene glycol di(meth)acrylate, and alkoxy polyalkylene glycol mono(meth)acrylate. Examples of the alkylene oxide group include an ethylene oxide group, a propylene oxide group, and a butylene oxide group.
[0035] The pressure-sensitive adhesive composition according to the present embodiment contains an antistatic agent. The antistatic agent according to the present embodiment is preferably an ionic compound, particularly preferably an ionic compound that is solid at a temperature of 25° C. and has a melting point of 25 to 50° C. Such an ionic compound is presumed to have a high affinity with the acrylic polymer because it has a low melting point and a long-chain alkyl group. It is preferable that the composition contains at least one or more of the ionic compounds as essential components in a ratio of 0.01 to 10 parts by weight in total per 100 parts by weight of the acrylic polymer.
[0036] The anion of the ionic compound is hexafluorophosphate (PF6 - ), thiocyanate (SCN - ), perchlorate (ClO4 - ), tetrafluoroborate (BF4 - ), inorganic anions such as carboxylates (RCOO -), sulfonates (RSO3 - ), alkoxide or phenoxide salts (RO - ), organic imide salts (R - ), methide salt (R3C - ), organic borate salts (R4B - ) and other organic anions. R included in each general formula of the organic anion is an organic group which may have a fluorine substitution. Examples of the organic group include at least one of an alkyl group, an alkoxy group, an aromatic group (aryl group, aralkyl group, etc.), an aliphatic or aromatic carbonyl group, and an aliphatic or aromatic sulfonyl group. In these organic groups, some or all of the hydrogen atoms may be substituted with fluorine atoms.
[0037] The cation of the ionic compound may be one selected from the group consisting of pyridinium, imidazolium, phosphonium, sulfonium, pyrrolidinium, guanidinium, ammonium, isouronium, thiouronium, piperidinium, pyrazolium, methylium, lithium, and morpholinium. When the anion and / or cation of the ionic compound contains an organic group such as an alkyl group, it is possible to obtain one having a melting point of 25 to 50° C. by selecting the chain length of the alkyl group, the position and number of the substituents, and the like.
[0038] The pressure-sensitive adhesive composition according to the present embodiment further contains a crosslinking agent. As the crosslinking agent, (D) a trifunctional or higher isocyanate compound is preferable. (D) Trifunctional or higher isocyanate compound includes, for example, biuret modified or isocyanurate modified diisocyanates such as hexamethylene diisocyanate, isophorone diisocyanate, diphenylmethane diisocyanate, tolylene diisocyanate, xylylene diisocyanate, and adducts with trivalent or higher polyols such as trimethylolpropane and glycerin. (D) The total of at least one trifunctional or higher isocyanate compound is preferably 0.1 to 10 parts by weight, more preferably 0.5 to 5 parts by weight, and particularly preferably 1 to 3 parts by weight, per 100 parts by weight of the acrylic polymer.
[0039] The pressure-sensitive adhesive composition according to the present embodiment may contain a crosslinking retarder (E). The crosslinking retarder (E) is preferably a keto-enol tautomer compound, and specific examples include β-ketoesters such as methyl acetoacetate, ethyl acetoacetate, octyl acetoacetate, oleyl acetoacetate, lauryl acetoacetate, and stearyl acetoacetate, and β-diketones such as acetylacetone, 2,4-hexanedione, and benzoylacetone. In a pressure-sensitive adhesive composition using a polyisocyanate compound as a crosslinking agent, these compounds block the isocyanate groups of the crosslinking agent, thereby suppressing excessive viscosity increase and gelation of the pressure-sensitive adhesive composition after the crosslinking agent is blended, and can extend the pot life of the pressure-sensitive adhesive composition. It is preferable that the crosslinking retarder (E) is contained in a ratio of 0.1 to 300 parts by weight per 100 parts by weight of the acrylic polymer.
[0040] The pressure-sensitive adhesive composition according to the present embodiment may contain a crosslinking catalyst other than a tin compound as the crosslinking catalyst (F). Examples of the crosslinking catalyst other than a tin compound include amine compounds such as tertiary amines and metal chelate compounds other than tin chelates. Examples of tertiary amines include trialkylamines, N,N,N',N'-tetraalkyldiamines, N,N-dialkylaminoalcohols, triethylenediamine, morpholine derivatives, and piperazine derivatives. The (F) crosslinking catalyst is preferably at least one metal chelate compound selected from the group consisting of aluminum chelate compounds, titanium chelate compounds, and iron chelate compounds. Specific examples of the metal chelate compound include tris(2,4-pentanedionato)iron(III), iron trisacetylacetonate, titanium trisacetylacetonate, aluminum trisacetylacetonate, tris(2,4-hexanedionato)iron(III), tris(2,4-hexanedionato)titanium, and tris(2,4-hexanedionato)aluminum. It is preferable that the crosslinking catalyst (F) is contained in an amount of 0.001 to 0.5 parts by weight based on 100 parts by weight of the acrylic polymer.
[0041] Since the (E) crosslinking retarder has an effect of suppressing crosslinking in contrast to the (F) crosslinking catalyst, it is preferable to appropriately set the ratio of the (E) crosslinking retarder to the (F) crosslinking catalyst. In order to extend the pot life of the pressure-sensitive adhesive composition and improve its storage stability, the (E) / (F) weight parts ratio is preferably 80 to 1000, more preferably 80 to 700, and particularly preferably 80 to 300. Here, the (E) / (F) weight parts ratio is the quotient value obtained by dividing the parts by weight of (E) by the parts by weight of (F).
[0042] The pressure-sensitive adhesive composition according to the present embodiment contains a deodorized and purified polyether-modified siloxane compound as the polyether-modified siloxane compound. The deodorized and purified polyether-modified siloxane compound is preferably contained in a ratio of 0.01 to 1.0 parts by weight, more preferably 0.01 to 0.8 parts by weight, per 100 parts by weight of the acrylic polymer. By blending the deodorized and purified polyether-modified siloxane compound in the pressure-sensitive adhesive composition, the adhesive strength and contamination resistance of the pressure-sensitive adhesive layer can be improved. Furthermore, the pressure-sensitive adhesive layer formed using the pressure-sensitive adhesive composition containing the deodorized and purified polyether-modified siloxane compound according to this embodiment has excellent contamination resistance that prevents contamination of the adherend surface.
[0043] A polyether-modified siloxane compound is a siloxane compound having a polyether group, and is a compound having a normal siloxane unit [-SiR 1 2-O-], as well as siloxane units with polyether groups [-SiR 1 (R 2 O(R 3 O) n R 4 )-O-], where R 1 is one or more alkyl or aryl groups, R 2 and R 3 is one or more alkylene groups, R 4 indicates one or more alkyl or acyl groups (terminal groups). The polyether group is a polyoxyethylene group [(C2H4O) n 〕 and polyoxypropylene group〔(C3H6O) n In the siloxane unit having a polyether group, the terminal of the polyether group is an OH group (R 4 =H).
[0044] Polyether-modified siloxane compounds can be obtained, for example, by grafting an organic compound having an unsaturated bond and a polyoxyalkylene group onto a polyorganosiloxane main chain having a silicon hydride group by a hydrosilylation reaction.Specific examples include dimethylsiloxane-methyl(polyoxyethylene)siloxane copolymer, dimethylsiloxane-methyl(polyoxyethylene)siloxane-methyl(polyoxypropylene)siloxane copolymer, and dimethylsiloxane-methyl(polyoxypropylene)siloxane polymer.
[0045] The present invention is characterized by using a polyether-modified siloxane compound which has been purified and deodorized by removing by-products. For example, in the hydrosilylation reaction, when an allyl-etherified polyoxyalkylene is used as an organic compound having an unsaturated bond and a polyoxyalkylene group, the by-product may generate a propenyl-etherified polyoxyalkylene by isomerization of the allyl group. Furthermore, propionaldehyde or its condensate (acetal, etc.) may be generated by hydrolysis of the propenyl ether group. Therefore, the deodorized and purified polyether-modified siloxane compound is preferably a polyether-modified siloxane compound obtained by removing the by-product propenyl-etherified polyoxyalkylene and / or aldehyde condensate. These by-products can be removed by acid decomposition, hydrogenation, etc. By using the deodorized and purified polyether-modified siloxane compound obtained by removing the above-mentioned by-products, the contamination resistance performance can be improved. The adhesive composition according to this embodiment does not contain a polyether-modified siloxane compound that has not been deodorized and purified, and therefore can be an adhesive composition that does not contain the above-mentioned by-products.
[0046] The HLB value of the polyether-modified siloxane compound is preferably in the range of 4 to 15. The HLB value is the hydrophilic-lipophilic balance (hydrophilic-lipophilic ratio) as defined in, for example, JIS K3211 (surfactant terminology) and the like. The molecular weight of the polyether-modified siloxane compound is preferably, for example, 10,000 or less as the weight average molecular weight (Mw). From the viewpoint of compatibility with acrylic polymers, the lower the HLB value and the lower the molecular weight, the better the compatibility. However, if the polyether-modified siloxane compound has a low molecular weight, it can obtain excellent antistatic performance even if it has a relatively high HLB value and a somewhat low compatibility with the polymer.
[0047] The adhesive composition of the present embodiment may contain, as appropriate, known additives such as surfactants, curing accelerators, plasticizers, fillers, curing retarders, processing aids, antioxidants, antioxidants, etc. These may be used alone or in combination of two or more kinds.
[0048] The pressure-sensitive adhesive composition of the present embodiment is suitable as a pressure-sensitive adhesive composition for a surface protection film to be attached to the surface base material of a polarizing plate (for example, a protective layer of a polarizer). Here, the protective layer of the polarizer of the polarizing plate may be one selected from the group consisting of a TAC-based film, a PMMA-based film, and a PET-based film. Here, TAC is an abbreviation for triacetyl cellulose, PMMA is an abbreviation for polymethyl methacrylate, and PET is an abbreviation for polyethylene terephthalate. The surface treatment applied to the protective layer of the polarizer of the polarizing plate may be one selected from the group consisting of untreated, AG treatment, LR treatment, AR treatment, AG-LR treatment, and AG-AR treatment, where AG stands for anti-glare, LR stands for low reflection, and AR stands for anti-reflection.
[0049] The pressure-sensitive adhesive composition of the present embodiment has a surface resistivity of 1.0×10 +12 It is preferable that the resistance is 5.0×10 +11 More preferably, it is 1.0×10 +11 It is particularly preferable that the surface resistivity is Ω / □ or less. If the surface resistivity is high, the performance of dissipating static electricity generated when peeling the adhesive layer from the adherend is poor. Therefore, by making the surface resistivity sufficiently small, the peeling electrification voltage caused by static electricity generated when peeling the adhesive layer from the adherend is reduced, and the influence on the adherend can be suppressed.
[0050] In the pressure-sensitive adhesive composition of the present embodiment, the pressure-sensitive adhesive layer formed by crosslinking the pressure-sensitive adhesive composition preferably has a peeling electrification voltage in the range of +0.3 to -0.3 kV with respect to a low refractive index layer formed using a composition for forming a low refractive index layer containing a fluorine compound. Examples of the fluorine compound used in the composition for forming a low refractive index layer include fluorine-containing copolymers which are polymers of one or more of fluorinated olefins, fluorinated vinyl ethers, fluorinated alkyl (meth)acrylates, etc., and condensates of fluorinated alkyl group-containing silane compounds. The fluorine-containing copolymer may be copolymerized with non-fluorinated monomers such as olefins, vinyl ethers, and (meth)acrylates in addition to fluorinated monomers. The low refractive index layer may be combined with a high refractive index layer to form an antireflection layer. Examples of the substrate on which the low refractive index layer is formed include at least one selected from triacetyl cellulose (TAC), polymethyl methacrylate (PMMA), polyethylene terephthalate (PET), etc. The peeling electrification voltage of the pressure-sensitive adhesive layer with respect to a low refractive index layer using PMMA as a substrate is preferably in the range of +0.3 to -0.3 kV.
[0051] The adhesive composition of the present embodiment is preferably free from contamination when an adhesive layer obtained by crosslinking the adhesive composition is attached to an adherend, left in an atmosphere at a temperature of 60° C. and a humidity of 90% RH for 2 days (48 hr), and removed from the atmosphere and one day later, the adhesive layer is peeled off from the adherend. Examples of the adherend include surface substrates such as PMMA substrates and TAC substrates, or low refractive index layers formed on the surfaces of the substrates using a composition for forming low refractive index layers containing a fluorine compound, or polarizing plates having such surface substrates or low refractive index layers.
[0052] The adhesive layer formed by crosslinking the adhesive composition of the present embodiment has an adhesive strength to an adherend of 0.04 to 0.2 N / 25 mm at a low peeling speed of 0.3 m / min, and preferably 2.0 N / 25 mm or less at a high peeling speed of 30 m / min, and more preferably 0.2 to 1.6 N / 25 mm. This provides performance with little change in adhesive strength depending on the peeling speed, and enables rapid peeling even at high-speed peeling. In addition, even when the surface protection film is peeled off from the adherend for re-adhesion, it does not require excessive force and is easy to peel off from the adherend. Examples of the adherend include surface substrates such as PMMA substrates and TAC substrates, or a low refractive index layer formed on the surface of the substrate using a composition for forming a low refractive index layer containing a fluorine compound, or a polarizing plate having such a surface substrate or low refractive index layer, such as a polarizing plate subjected to low reflection (LR) surface treatment and a polarizing plate subjected to AG-LR treatment.
[0053] The gel fraction of the pressure-sensitive adhesive layer obtained by crosslinking the pressure-sensitive adhesive composition of the present embodiment is preferably 95 to 100%, more preferably 97 to 100%. Such a high gel fraction of the pressure-sensitive adhesive layer prevents the adhesive strength from becoming excessively high at a low peeling speed. In addition, the amount of unpolymerized monomer or oligomer eluted from the copolymer contained in the pressure-sensitive adhesive composition is reduced, improving durability at high temperature and high humidity, and contributing to suppressing contamination of the adherend.
[0054] The adhesive film of the present embodiment is formed by forming an adhesive layer formed by crosslinking the adhesive composition of the present embodiment on one side or both sides of a resin film. The surface protection film of the present embodiment is a surface protection film formed by forming the adhesive layer on one side of a resin film. The adhesive composition of the present embodiment has excellent antistatic performance, has an excellent balance of adhesive strength at low peeling speed and high peeling speed, and also has excellent anti-staining performance. Therefore, it can be suitably used as a surface protection film for a polarizing plate.
[0055] As the base film of the pressure-sensitive adhesive layer and the release film (separator) that protects the adhesive surface, a resin film such as a polyester film can be used. One side of the resin film may be subjected to antistatic treatment and antifouling treatment on the side opposite to the side on which the pressure-sensitive adhesive layer is formed. Antistatic treatment may include coating or kneading of an antistatic agent. Antifouling treatment may include treatment with a silicone-based or fluorine-based release agent or coating agent, silica fine particles, etc. The release film may be subjected to release treatment with a silicone-based, fluorine-based, or long-chain alkyl-based release agent on the side that is to be joined to the adhesive surface of the pressure-sensitive adhesive layer.
[0056] In addition, an optical film with a pressure-sensitive adhesive layer can be obtained by laminating a pressure-sensitive adhesive layer obtained by crosslinking the pressure-sensitive adhesive composition of the present embodiment on at least one surface of an optical film. Examples of optical films include polarizing films, retardation films, anti-reflection films, anti-glare films, ultraviolet absorbing films, infrared absorbing films, optical compensation films, and brightness enhancing films. Examples of devices to which optical members are applied include liquid crystal panels, organic EL panels, and touch panels. In the case of optical surface protection films such as surface protection films for polarizing plates and pressure-sensitive adhesive films, the base film and pressure-sensitive adhesive layer preferably have sufficient transparency. EXAMPLES
[0057] The present invention will be specifically described below with reference to examples.
[0058] <Production of acrylic polymer> [Example 1] Nitrogen gas was introduced into a reactor equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen inlet tube, and the air in the reactor was replaced with nitrogen gas. Then, 100 parts by weight of 2-ethylhexyl acrylate, 4.0 parts by weight of 8-hydroxyoctyl acrylate, 0.1 parts by weight of acrylic acid, and a solvent (ethyl acetate) were added to the reactor. Then, 0.1 parts by weight of azobisisobutyronitrile as a polymerization initiator was dropped over 2 hours, and the mixture was reacted at 65°C for 6 hours to obtain an acrylic polymer used in Example 1. [Examples 2 to 6 and Comparative Examples 1 to 3] The acrylic polymer solutions used in Examples 2 to 6 and Comparative Examples 1 to 3 were obtained in the same manner as the acrylic polymer solution used in Example 1 above, except that the monomer compositions were as shown in Table 1 (A) to (C). The weight average molecular weights (Mw) of the acrylic polymers of Examples 1 to 6 and Comparative Examples 1 to 3 are shown in Table 2.
[0059] <Production of Pressure-Sensitive Adhesive Composition and Surface Protective Film> [Example 1] To the acrylic polymer solution of Example 1 produced as described above, 2.0 parts by weight of a crosslinking agent (Coronate HX), 9.0 parts by weight of a crosslinking retarder (acetylacetone), 0.1 parts by weight of a crosslinking catalyst (titanium trisacetylacetonate), 0.9 parts by weight of an antistatic agent (4-methyl-1-octylpyridinium hexafluorophosphate), and 0.05 parts by weight of an odorless purified polyether modified siloxane compound (KF-6017P (odorless type), HLB value = 5) were added and mixed by stirring to obtain an adhesive composition of Example 1. This adhesive composition was applied onto a release film (a silicone resin-coated PET film), and then dried at 90 ° C. to remove the solvent, thereby obtaining an adhesive layer having a thickness of 20 μm. Thereafter, the adhesive layer with a release film was transferred to the side of the base film (a PET film with one side treated for antistatic and antifouling) opposite the side treated for antistatic and antifouling, thereby obtaining the surface protection film of Example 1 having a laminate structure of "base film / adhesive layer / release film". [Examples 2 to 6 and Comparative Examples 1 to 3] Surface protection films of Examples 2 to 6 and Comparative Examples 1 to 3 were obtained in the same manner as the surface protection film of Example 1 above, except that the compositions of the additives were changed as shown in Table 1 (D) to (H), respectively.
[0060] [Table 1]
[0061] [Table 2]
[0062] In Table 1, the parts by weight of each component were calculated assuming the total of (A) to be 100 parts by weight. In addition, in each of columns (D) to (H), the parts by weight of each component, calculated assuming the acrylic polymer to be 100 parts by weight, are shown in parentheses ( ). The compound names of the abbreviations of each component used in Table 1 are shown in Table 3. Coronate (registered trademark) HX, Coronate (registered trademark) HL, and Coronate (registered trademark) L are product names of Tosoh Corporation, and Takenate (registered trademark) D-140N is a product name of Mitsui Chemicals, Inc. G-1 to G-5 in Table 3 are ionic compounds having a melting point of 25 to 50° C. (solid at room temperature), and G-6 is an ionic compound having a melting point of more than 50° C. (solid at room temperature). The HLB value and the trade name are listed in column (H) of Table 3. H-1 and H-3 to H-6 are trade names of Shin-Etsu Chemical Co., Ltd., and H-2 is a trade name of Dow Corning Toray Co., Ltd. The weight average molecular weight (Mw) of H-1 to H-4 was all 10,000 or less, the Mw of H-5 was 20,000, and the Mw of H-6 was 30,000.
[0063] [Table 3]
[0064] <Test methods and evaluation> The surface protection films of Examples 1 to 6 and Comparative Examples 1 to 3 were each aged for 7 days in an atmosphere at a temperature of 23° C. and a humidity of 50% RH, and then evaluated by the following test method.
[0065] <Adhesive strength test method> The release film was peeled off to expose the adhesive layer, and the surface protection film was attached to the surface of a polarizing plate via the adhesive layer, and after leaving it for one day, it was autoclaved at 50°C and 5 atm for 20 minutes and left at room temperature for another 12 hours to prepare a sample for measuring adhesive strength. The obtained sample was peeled off in the 180° direction at a low speed (0.3 m / min) or a high speed (30 m / min) using a tensile tester, and the peel strength was measured and used as the adhesive strength.
[0066] <Surface resistivity test method> After aging the surface protection film and before bonding to a polarizing plate, the release film was peeled off to expose the adhesive layer, and the surface resistivity of the adhesive layer was measured using a resistivity meter Hiresta UP-HT450 (manufactured by Mitsubishi Chemical Analytech).
[0067] <Test method for peeling electrification voltage> The release film was peeled off to expose the pressure-sensitive adhesive layer, and the surface protection film was attached to a polarizing plate having a low refractive index layer formed on the adhesion surface using a composition for forming a low refractive index layer containing a fluorine compound. When the surface protection film was peeled off at 180° at a pulling speed of 30 m / min, the voltage (charged voltage) generated by the adhesion was measured using high-precision static electricity sensors SK-035 and SK-200 (manufactured by Keyence Corporation), and the maximum measured value was taken as the peeling charged voltage.
[0068] <Test method for stain resistance> A polarizing plate that had been subjected to low reflection (LR) surface treatment was attached to one side of a glass plate via an adhesive layer (double-sided adhesive tape) using a laminator. Then, a surface protection film was attached to the surface of the polarizing plate using a laminator. After attachment to the adherend, the plate was left in an atmosphere of 60°C temperature and 90% RH humidity for 2 days (48 hrs), and after one day had passed since being removed from the atmosphere, the surface protection film was peeled off from the adherend, and the contamination state of the polarizing plate surface was visually observed. The criteria for the stain resistance performance were as follows: no stain on the surface of the polarizing plate was evaluated as "○", slight stain was evaluated as "△", and stain was evaluated as "×".
[0069] <Odorlessness test method> In the stain resistance test, when the surface protection film was peeled off from the adherend, the surface of the adhesive layer of the peeled surface protection film and the surface of the polarizing plate were smelled and the degree of odor was evaluated. When peeled off, the case where there was no particular odor was rated as "◯", when there was a slight odor was rated as "△", and when there was a particular odor was rated as "X". The impurities contained in the polyether-modified siloxane compound, the by-product propenyl-etherified polyoxyalkylene and aldehyde condensation products, are contained in such extremely small amounts that they cannot be measured by instrumental analysis, and therefore an odorlessness test is used to determine whether the polyether-modified siloxane compound has been purified to remove odors.
[0070] Table 4 shows the evaluation results of various tests for the surface protection films of Examples 1 to 6 and Comparative Examples 1 to 3. "Surface resistivity" is "m×10 +n " is expressed as "mE+n" (where m is any real value and n is a positive integer). The column "Anti-soiling performance" shows the material (PMMA) and surface treatment (AG-LR) of the surface base material of the polarizing plate used in the performance tests of the surface protective films of Examples 1-6 and Comparative Examples 1-3.
[0071] [Table 4]
[0072] The surface protection films of Examples 1 to 6 had an adhesive strength of 0.04 to 0.2 N / 25 mm at a slow peel speed of 0.3 m / min to a polarizing plate as an adherend, and an adhesive strength of 2.0 N / 25 mm or less at a fast peel speed of 30 m / min, demonstrating excellent adhesive performance. In addition, the surface protective films of Examples 1 to 6 had a surface resistivity of the pressure-sensitive adhesive layer of 1.0×10 +12 The peeling charge voltage of the adhesive layer against an adherend of a low refractive index layer formed using a composition for forming a low refractive index layer containing a fluorine compound was within the range of +0.3 to -0.3 kV, and the antistatic performance was excellent. Furthermore, the surface protection films of Examples 1 to 6 were attached to an adherend, and then left in an atmosphere of 60°C and 90% RH for two days. After being removed from the atmosphere and one day later, the surface protection films were not contaminated when peeled off from the adherend, and also had excellent contamination resistance. In other words, the evaluation results shown in Table 4 prove that the surface protection films of Examples 1 to 6 are able to solve the problems of the present invention.
[0073] In the surface protection films of Comparative Examples 1 to 3, the antistatic performance and the anti-staining performance against the above-mentioned adherend were poor, probably because the adhesive composition contained a polyether-modified siloxane compound that was not deodorized and refined. In particular, Example 1 and Comparative Example 1 have the same composition ratio of acrylic polymer, and there is a difference in the anti-staining performance between Example 1, which contains a polyether-modified siloxane compound that has been deodorized and Comparative Example 1, which contains a polyether-modified siloxane compound that has not been deodorized and refined. Furthermore, in the surface protection film of Comparative Example 3, the adhesive strength at both a low peeling speed of 0.3 m / min and a high peeling speed of 30 m / min were too high, so the adhesive performance of the adhesive layer was also poor. Thus, the surface protection films of Comparative Examples 1 to 3 could not solve the problems of the present invention.
Claims
1. The pressure-sensitive adhesive composition includes an acrylic polymer mainly composed of an alkyl (meth)acrylate ester, an antistatic agent, a crosslinking agent, and a polyether-modified siloxane compound, the antistatic agent is an ionic compound, the cation of the ionic compound is one selected from the group consisting of pyridinium, imidazolium, phosphonium, sulfonium, pyrrolidinium, guanidinium, ammonium, isouronium, thiouronium, piperidinium, pyrazolium, methylium, lithium, and morpholinium; the polyether-modified siloxane compound is a deodorized and refined polyether-modified siloxane compound, and the deodorized and refined polyether-modified siloxane compound is contained in a ratio of 0.01 to 1.0 part by weight per 100 parts by weight of the acrylic polymer; The pressure-sensitive adhesive layer obtained by crosslinking the pressure-sensitive adhesive composition has a surface resistivity of 1.0×10 +12 A pressure-sensitive adhesive composition having a surface tension of Ω / □ or less.
2. The pressure-sensitive adhesive composition according to claim 1, characterized in that the deodorized and purified polyether-modified siloxane compound is a polyether-modified siloxane compound having an HLB value of 4 to 15 and a weight average molecular weight of 10,000 or less, from which by-product propenyl-etherified polyoxyalkylene and / or aldehyde condensates have been removed.
3. 3. A pressure-sensitive adhesive film comprising a resin film and a pressure-sensitive adhesive layer formed by crosslinking the pressure-sensitive adhesive composition according to claim 1 or 2 laminated on one side of the resin film.
4. A surface protection film comprising the pressure-sensitive adhesive film according to claim 3.
5. A surface protection film for a polarizing plate, comprising the pressure-sensitive adhesive film according to claim 3 .
6. 3. An optical film with a pressure-sensitive adhesive layer, comprising an optical film and a pressure-sensitive adhesive layer formed by crosslinking the pressure-sensitive adhesive composition according to claim 1 or 2 laminated on at least one surface of the optical film.
7. The pressure-sensitive adhesive film according to claim 3 , wherein one surface of the resin film opposite to the surface on which the pressure-sensitive adhesive layer is formed is subjected to an antistatic treatment and an antifouling treatment.
Citation Information
Patent Citations
Device for assembling electric equipment
JP1980044800A
Washer for filler
JP1985058390A
Production of silicone polyether copolymer having reduced smell
JP2000327785A
Pressure-sensitive adhesive composition, pressure-sensitive adhesive layer, and pressure-sensitive adhesive sheet
JP2010202692A
Method for producing low-odor glycerol derivative-modified silicone or composition containing the same
JP2013151658A